2009
DOI: 10.2319/100708-525r.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of First Premolar Extraction on Mandibular Third Molar Angulation

Abstract: Objective:To compare the angular changes in the developing mandibular third molars in both first premolar extraction and nonextraction cases and to determine whether premolar extraction results in a more mesial movement of the mandibular buccal segment and causes favorable rotational changes in the mandibular third molar tilt, which can enhance later eruption of the third molars. Materials and Methods: Pretreatment (T1) and posttreatment (T2) panoramic radiographs were taken of 25 subjects who had been treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 14 publications
2
30
1
1
Order By: Relevance
“…Our results coincide with those obtained by Haavikko et al (24) who claims that extractions of mandibular premolars accelerated, but did not favour, the eruption of the mandibular third molars. Nevertheless, other authors such as Richardson et al (5), Kim et al (6) or Jain et al (25), observed that the extraction of premolars made more space in the molar area and, therefore, improved the angulation of the mandibular third molar compared to patients treated without extractions. Changes in the gonial angle.…”
Section: Discussionmentioning
confidence: 96%
“…Our results coincide with those obtained by Haavikko et al (24) who claims that extractions of mandibular premolars accelerated, but did not favour, the eruption of the mandibular third molars. Nevertheless, other authors such as Richardson et al (5), Kim et al (6) or Jain et al (25), observed that the extraction of premolars made more space in the molar area and, therefore, improved the angulation of the mandibular third molar compared to patients treated without extractions. Changes in the gonial angle.…”
Section: Discussionmentioning
confidence: 96%
“…In the group of male subjects, mesioangulation of the third mandibular molar was observed, this being significantly greater on the right side. However, some authors such as Jain (22) (2009) and Ahmed (23) (2011) have found large differences in this angle between patients regardless of whether or not they had performed premolar extractions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 20 teeth were treated using a combination of surgical exposure and orthodontic traction. Some authors such as Kim et al (20), Jain et al (21) observed that prob ability of mandibular third molar eruption is related to premolars extraction. In contrast, Tarazona et al (22) demonstrated that the angulation of third molar improves with time regardless of treatment, and presents a greater disinclusion in cases treated with extractions.…”
Section: Discussionmentioning
confidence: 99%